2020
DOI: 10.1287/msom.2019.0793
|View full text |Cite
|
Sign up to set email alerts
|

Nonbinding Goals in Teams: A Real Effort Coordination Experiment

Abstract: Problem definition: We investigate the impact of nonbinding (wage-irrelevant) goals, set by a manager, on a team of workers with “weak-link” production technology. Can nonbinding goals improve team production when team members face production complementarity? Academic/practical relevance: Nonbinding goals are easy to implement and ubiquitous in practice. These goals have been shown to improve individual performance, but it remains to be seen if such goals are effective in team production when there is producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…(2008) and demonstrated that assigned goals should be challenging but attainable, and monetary incentives can magnify the motivational effects of goal setting. Fan and Gómez-Miñambres (2020) examined the effects of an assigned goal on team production using a coordination game with a goal-dependent non-monetary utility.…”
Section: Related Literaturementioning
confidence: 99%
“…(2008) and demonstrated that assigned goals should be challenging but attainable, and monetary incentives can magnify the motivational effects of goal setting. Fan and Gómez-Miñambres (2020) examined the effects of an assigned goal on team production using a coordination game with a goal-dependent non-monetary utility.…”
Section: Related Literaturementioning
confidence: 99%
“…In essence, our supplier game resembles the weakest link coordination in the economic literature (Cooper & Weber, 2020; Van Huyck et al, 1990). In the area of operations management, the complementary relationship has been widely investigated in assembly systems (Davis et al, 2022; Hyndman et al, 2013) and teamwork (Bansal & Gutierrez, 2020; Fan & Gómez‐Miñambres, 2020; Shokoohyar et al, 2019). We add to this literature by exploring the horizontal coordination among complementary suppliers and identify whether the vertical information dissemination by a buyer can help the supplier coordination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In essence, our supplier game resembles the weakest link coordination in the economic literature (Cooper & Weber, 2020;Van Huyck et al, 1990). In the area of operations management, the complementary relationship has been widely investigated in assembly systems (Davis et al, 2022;Hyndman et al, 2013) and teamwork (Bansal & Gutierrez, 2020;Fan & G omez-Miñambres, 2020;Shokoohyar et al, 2019). We add to this literature by exploring the horizontal coordination among complementary suppliers and identify whether the vertical information dissemination by a buyer can help the supplier coordination.…”
Section: Supplier Bottleneckmentioning
confidence: 99%